ANTIBIOTICS SENSITIVITY PATTERN OF FOOD-BORNE BACTERIA AMONGST CARRIERS, FOOD HANDLERS IN A NIGERIAN UNIVERSITY - Cornelius O. Ogu; Rita I-O. Ogu
Antibiotics sensitivity patterns of food-borne bacteria amongst food handlers in a Nigerian University was carried out in this study. 100 food handlers actively participated in this research. Percutaneous and nasal swabs were collected and samples were placed on MacConkey, blood and chocolate agar media, incubated at 37 0 C for 24 h, followed by biochemical identification of isolates. Antibiotics multi-disc were used to test bacteria susceptibility. Among bacteria isolates, 14% showed very poor sensitivity. Sensitivity to ampicillin, flucloxacillin, rifampicin and streptomycin was < 50%. Prevalence of food-borne pathogens was 76 % for percutaneous and 51 % for nasal samples. Isolates-sex difference was not statistically significant p > 0.05. Staphylococci isolates had the highest prevalence, 64 % and 45 % from percutaneous and nasal samples, respectively. Thirty (30 %) participants had similar isolates from both sampling regions. Antibiotics multi-resistant strains of bacteria are prevalent in our environment. Food handlers can be potential reservoirs and means of transmission of antibiotics multi-resistant food-borne bacteria.